Benchmarking State-of-the-Art Large Language Models for Migraine Patient Education: Performance Comparison of Responses to Common Queries - Linger Li; Pengfei Li; Kun Wang; Liang Zhang; Hongwei Ji; Hongqin Zhao (JMIR Publications, 2024)
This study assessed the potential of large language models (OpenAI's ChatGPT 3.5 and 4.0, Google Bard, Meta Llama2, and Anthropic Claude2) in addressing 30 common migraine-related queries, providing a foundation to advance artificial intelligence-assisted patient education and insights for a holistic approach to migraine management.